Acute community acquired pneumonia: 96 cases in Madagascar - Rakotoson, J L; Rakotomizao, J R; Andrianarisoa, A C F (Médecine tropicale, 2010)
The purpose of this report is to describe a study on acute community-acquired pneumonia (CAP) carried out in the Pneumology Department of the Antananarivo University Hospital Center. This prospective one-year study included patients presenting symptoms of acute CAP. Patients with chronic lung disease and tuberculosis were excluded. Study parameters included epidemiological, clinical and laboratory findings as well as data on the efficacy of the therapeutic treatments used. A total of 96 patient charts were analyzed. Males were predominant with a sex ratio of 1.5. Mean age was 41.8 years. A history of pulmonary tuberculosis was noted in 7.2% of cases. Clinical examination showed pulmonary condensation in 93.7% of cases. Radiological examination depicted alveolar syndrome in 97.6%. Betalactamines were the most frequent class of antibiotic agents used for treatment (90.6%). The most frequently prescribed agent was amoxicillin (60.4%) at a dose of 3 g/day. Single-agent therapy was used more often than double-agent therapy (93.7% vs. 6.3%). The oral route was used more frequently than the intravenous route (62.5% vs. 37.5%). The outcome was favorable in 97.9% of cases and lethal in 2.1%. The prevalence of acute CAP in patients hospitalized in our department was low in comparison with that tuberculosis. Since single-agent therapy using amoxicillin at a dose of 3 g/day was effective, this antibiotic can be recommended as the first-line treatment after ruling out tuberculosis.